An analysis of the global burden of gallbladder and biliary tract cancer attributable to high BMI in 204 countries and territories: 1990–2021 - Hu, Zhuowen; Wang, Xue; Zhang, Xin; Sun, Wuping; Mao, Jun (Frontiers in Nutrition, 2024)
BackgroundGallbladder and biliary tract cancers (GBTCs) are aggressive with poor prognosis, often undetected until advanced stages. High Body Mass Index (BMI) is a significant risk factor, contributing substantially to GBTC mortality and Disability-Adjusted Life Years (DALYs). This study aimed to quantify the global burdens of GBTCs attributable to high BMI from 1990 to 2021, thereby developing more rational prevention and treatment strategies for GBTC.MethodsData were extracted from the Global Burden of Disease (GBD) 2021. Age-standardized rates of mortality (ASMR), and DALYs (ASDR) for GBTCs due to high BMI were calculated by years, genders, ages, geographical locations, and sociodemographic index (SDI). The estimated annual percentage change (EAPC) was calculated to evaluate the temporal trends from 1990 to 2021. Decomposition and frontier analyses were conducted to understand the driving forces behind burden changes and to identify top-performing countries. Inequality analysis was conducted to assess burden disparities across different SDI levels. The disease burden was forecasted through 2035 using the Bayesian age period cohort (BAPC) model.ResultsGlobally, ASMR and ASDR for GBTCs related to high BMI decreased from 1990 to 2021; however, the absolute number of deaths and DALYs cases more than doubled, and similar patterns are projected to continue over the next 14 years in the absence of intervention. High SDI regions showed higher burdens due to higher obesity rates, population growth, and aging, while low SDI regions faced higher EAPCs due to limited resources. Moreover, this inequality has become more significant. Females were more susceptible across all age groups. Notable variations in burden management were observed among countries, with some low SDI nations demonstrating superior performance to high SDI countries.ConclusionDespite the decline in rates, the burden of GBTCs attributable to high BMI remains substantial, underscoring the need for targeted prevention strategies for high BMI, particularly in high SDI regions. Gender and age disparities necessitate tailored health interventions.